2015
DOI: 10.1007/s00330-015-3903-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of degenerative and spondyloarthritis-related magnetic resonance imaging findings in the spine and sacroiliac joints in patients with persistent low back pain

Abstract: • The location of vertebral endplate signal changes supports a mechanical aetiology. • Several sacroiliac joint findings were associated with female gender and pregnancy-related back pain. • Sacroiliac joint bone marrow oedema was frequent and age-associated, indicating a possible degenerative aetiology. • More knowledge of the clinical importance of sacroiliac joint MRI findings is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
81
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 87 publications
(94 citation statements)
references
References 47 publications
10
81
0
Order By: Relevance
“…On the other hand, the other hand, a recent Danish study showed that all degenerative spinal findings were most frequent in men. This was explained by heavy work being more frequent among Danish men compared with women (Arnbak et al 2015). This current study demonstrated that spinal canal pathology was mostly prevalent in the 60-70-year age group.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…On the other hand, the other hand, a recent Danish study showed that all degenerative spinal findings were most frequent in men. This was explained by heavy work being more frequent among Danish men compared with women (Arnbak et al 2015). This current study demonstrated that spinal canal pathology was mostly prevalent in the 60-70-year age group.…”
Section: Discussionmentioning
confidence: 49%
“…Degenerative spinal disease tended to occur more common in males but there was no statistically significant difference. Furthermore, a statistically significant difference was noted between gender and fractures found on MRI post-lumbosacral spine X-ray 2 (1, n = 1000) = 4.64, p = 0.031, phi = -.068. Fractures found on MRI investigation occurred in male primary care patients.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations